AKULTURASI BUDAYA SUNDA DAN MUNA DALAM KELUARGA DI DESA MEKAR JAYA KECAMATAN TIWORO KABUPATEN MUNA BARAT - Pintra Risalah; La Ode Topo Jers; La Janu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2019)
This study aimed to determine the form of acculturation in mixed marital households in West Java and local communities in the village of Mekar Jaya, Tiworo Sub-district, West Muna Regency. Also, to know cultural reproduction in the household. Informants in this study were determined by purposive sampling. Data collection is done using field research methods through observation techniques and in-depth interviews. The results of this study indicate that some forms of acculturation that occur in mixed households appear in: (a) the language/dialect used in the family; (b) food consumed by family members and (c) certain habits (shared eating habits). Cultural construction in the household of mixed marriages occurs because family members often carry out joint activities and see their habits. These conditions make family members adjust to each other and slowly tend to follow the habits carried out by husband/wife partners with each other